Model Regresi Nonparametrik Spline Truncated Pada Angka Kematian Bayi di Provinsi Nusa Tenggara Timur - Pulo, Miltiades Dewifortuna; Suciptawati, Ni Luh Putu; Susilawati, Made (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to model the Infant Mortality Rate (IMR) in East Nusa Tenggara Province using truncated spline nonparametric regression. In this study, IMR is associated with four predictor variables: the percentage of poor people, the percentage of pregnant women under 19 years of age, low birth weight, and life expectancy. These four variables have an unpatterned relationship, indicating the presence of a nonparametric component in the model. The truncated spline regression method was chosen because of its ability to handle nonlinear relationships between variables. The results showed that the best model was obtained using three knot points, which produced a coefficient of determination (R²) of 97.47%. This indicates that the truncated spline regression model is able to explain 97.47% of the variation in IMR in East Nusa Tenggara Province. In addition, the four predictor variables have a significant influence on the model, making a significant contribution in explaining the factors that influence IMR in the region.